Męskie gimnazja państwowe we Lwowie w latach 1772–1914 - Gajak-Toczek, Małgorzata (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2010)
The purpose of this article is proposing of development state-owned secondary schools for men in Lvov from 1772 to 1914. First of all we should remember that this city was incorporated into the Austrian Empire during the First Partition of Poland and it was the capital of the largest part of Austria named the Kingdom of Galicia and Lodomeria. Despite of the fact, that gymnasiums were under strange power, they were a breeding ground for Polish intelligentsia, especially during the autonomy period.We should preserve a memory of them, because numerous well-known and famous people graduated from those schools who were reconstituted the Republic of Poland.